Integrating the Acehnese folklore and augmented reality to enhance EFL speaking - Nurjannah Nurjannah; Intan Zuhra; Muhammad Darwis; Suci Maulina; Junaidi Salat; Khairuddaraini Khairuddaraini (English Learning Innovation, 2026)
This study investigated the effectiveness of integrating Acehnese folklore Amat Rahmanyang into an Augmented Reality (AR) based learning environment to enhance English as a foreign language (EFL) learners’ speaking skills. Despite growing evidence supporting AR in language learning, Indonesia has explored the pedagogical integration of culturally grounded content, particularly local folklore from underrepresented communities like Aceh. This mixed methods study involved 25 first-grade students at SMA IT Al-Uswah, Sigli, Indonesia. It employed a one-group quasi-experimental design, combining pre-test and post-test assessments with thematic analysis of student interviews. The intervention utilized an AR application featuring the Acehnese tale of Amat Rahmanyang, delivered through interactive 3D animations, audio narration, and visual storytelling tasks. Speaking performance was evaluated using a CEFR-based analytic rubric. Quantitative findings indicated a significant improvement in students’ speaking scores, with mean scores rising from 10.24 (A2 level) to 17.00 (B1 level), confirmed by a paired sample t-test (t = 15.89, p < 0.001). Qualitative data revealed increased learner confidence, enhanced cultural engagement, and greater awareness of pronunciation and vocabulary use. Students expressed that familiarity with the folklore made speaking tasks more meaningful and reduced anxiety. The study concludes that integrating culturally familiar stories within AR-enhanced instruction provides not only linguistic benefits but also emotional and cultural relevance, fostering a more engaging and effective learning environment.